3D-printable colloidal photonic crystals. (June 2022) - Liao, Junlong; Ye, Changqing; Guo, Jie; Garciamendez-Mijares, Carlos Ezio; Agrawal, Prajwal; Kuang, Xiao; Japo, Julia Olga; Wang, Zixuan; Mu, Xuan; Li, Wanlu; Ching, Terry; Mille, Luis Santiago; et al.
Graphical abstract: Abstract: The architecture of the colloidal photonic crystals (CPCs) is of paramount importance to their functionality and applications. Nevertheless, the realization of CPCs with arbitrarily designed, volumetrically sophisticated structures at the macroscale remains challenging. In this work, a printable CPC ink was developed. By combining this ink with a digital light processing (DLP)-based three-dimensional (3D) printing system, we were able to fabricate the CPC superstructures featuring both digitally defined macroscale geometries and structural colors originating from the ordered structures at the sub-micron scale. Moreover, besides the arbitrarily adjustable and precisely designable architectures, the optical properties, mechanical performances, and stimuli-responsiveness of the printed objects could also be facilely tuned by the composition of the ink or the printing parameters of the DLP system. This technology endows us the ability to fabricate CPCs with a multitude of desirable functions as well as mimic the hierarchical structures and color-manipulation strategies of some creatures in nature, which paves the way for potentially broad applications in intelligent color displays, 3D integrated sensors, biomimetic color-morphing soft robots, and smart anti-counterfeiting labels, among others.